STUDI KUALITAS DAN BIAYA PRODUKSI BAMBU LAMINA SKALA PABRIK - Deazy Rachmi Trisatya; Achmad Supriadi; Ignasia Maria Sulastiningsih (Jurnal Penelitian Hasil Hutan, 2022)
Bamboo can be harvested faster than wood. Bamboo processing industry has been able to process bamboo into laminatedbamboo products by utilizing lamination technology. Laminated bamboo products derived from the bamboo processing industrymust be of high quality in order to suit their intended use. The purpose of this paper was to provide information on the physicaland mechanical properties, as well as the production costs, of laminated bamboo from one of Bali's laminated bamboo factories.The mechanical and physical properties of laminated bamboo flooring samples were tested in this study. The factory's productioncosts component data were calculated to obtain the estimate of production costs, product cost, and gross profit for laminatedbamboo flooring. The results of the tests showed that the laminated bamboo's moisture content and bonding quality meet therequirements of the Indonesian Standard for Laminated Bamboo for General Use and the International Standard for BambooFlooring for Indoor Use. The flexural strength of laminated bamboo met the requirements of both the Japanese Glued LaminatedTimber Standard and the International Standard for Bamboo Flooring for Indoor Use. This factory's laminated bamboo isequivalent to strength class III to strength class II of wood. The annual production of laminated bamboo for flooring is 9,600 m2,with a laminated bamboo production cost of Rp 262,905.21 per m2. With a typical selling price of Rp. 400,000.00 per m2, fora total gross income of Rp. 137,094.79 per m2, the gross profit to cost of production ratio is 0.52 and the gross profit to sellingprice ratio is 0.34.